2023
DOI: 10.1128/spectrum.04614-22
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus Species and Their Biosurfactants Eliminate Acinetobacter baumannii Biofilm in Various Manners

Abstract: A. baumannii biofilm is a significant virulence factor that causes the biofilm colonization of invasive illnesses. Rising bacterial resistance to synthetic antimicrobials has prompted researchers to look at natural alternatives, such as probiotics and their derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The antagonistic or antimicrobial effect of LAB against pathogens has been well documented in the literature ( 5 , 9 ). However, studies on the antimicrobial activity of LAB and/or its extracellular products against A. baumannii are currently limited ( 7 , 9 , 27 ). In the present work we observed a strong inhibitory activity of the LAB Lcb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antagonistic or antimicrobial effect of LAB against pathogens has been well documented in the literature ( 5 , 9 ). However, studies on the antimicrobial activity of LAB and/or its extracellular products against A. baumannii are currently limited ( 7 , 9 , 27 ). In the present work we observed a strong inhibitory activity of the LAB Lcb.…”
Section: Discussionmentioning
confidence: 99%
“…rhamnosus can lead to the disruption or disintegration of the A. baumannii cell envelope. Additionally, these authors observed the emergence of filament-like structures, which can serve as sites for the excessive leakage of vital cytoplasmic contents ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that the observed effect was mainly exerted by lactic acid and acetic acid, which showed a strong anti-A. baumanii bactericidal effect [106]. In another study, the authors demonstrated that the Lactobacillus plantarum strain was able to interfere with P. aeruginosa infections by suppressing QS, adhesion, and biofilm formation.…”
Section: Biofilm Wound Treatmentmentioning
confidence: 98%